Study on Bacterial Diversities in Stored Water under Different Storage Environments. Issue 6 (May 2019) - Zhang, Yaojun; Mei, Shaofeng; Li, Yunlong; Bi, Qingbo; Yang, Zifan; Wang, Yi; Chen, Xiao; Li, Xin
Abstract: Stored water is one kind of survival supply in emergency preparedness, which should be biologically safe during a certain storage period. Different storage environments including temperature and condition of sealing decide the microbial quality of water. An orthogonal test were conducted to discover the regulation of biological diversities in stored water for a period of 15 days. Growth-dose-response model were applied into the growth phase to simulate the bacterial growth. Statistical analysis revealed that: (1) nutrients including AOC determined the maximum values of HPC; (2) Temperature played its role through affect the growth rate of bacterium. (3) Under sealing conditions, water sample could keep biological stability for longer time, compared with unsealing surroundings.